Enhanced nerve function recovery in radial nerve palsy patients with humerus shaft fracture: a randomized study of low-frequency pulse electrical stimulation combined with exercise therapy - Shi, Shaoyan; Ou, Xuehai; Du, Xiaolong (Frontiers in Neurology, 2024)
Objective To evaluate the effect of low-frequency pulse electrical stimulation plus exercise therapy on nerve function recovery in patients with radial nerve palsy after humerus shaft fracture. Methods A total of 110 patients with humerus shaft fracture and radial nerve injury admitted to our hospital from January 2017 to December 2021 were recruited. They were randomized to receive either conventional exercise therapy (control group) or conventional exercise therapy plus low-frequency pulse electrical stimulation (study group) according to the random number table method, with 55 cases in each. Clinical efficacy, muscle strength recovery, nerve conduction velocity (MCV), amplitude, wrist joint, and elbow joint activities of patients were analyzed and compared. Results Patients with low frequency stimulation (LFS) showed significantly higher treatment effectiveness (89.09%) than those with exercise therapy only (69.09%). The incorporation of LFS with exercise therapy provided more enhancement in the muscle strength of wrist extensor and total finger extensor in patients when compared with a mere exercise intervention, suggesting better muscle function recovery of patients produced by LFS. Moreover, a significant increase in MCV and its amplitude was observed in all included patients, among which those receiving LFS showed a greater escalation of MCV and its amplitude. Following a treatment duration of 6 months, more patients in the LFS cohort were reported to achieve a wrist extension and elbow extension with an angle over 45° than the controls. There was no notable variance in adverse responses noted between the two patient groups. Conclusion In patients afflicted with humerus shaft fracture and radial nerve injury, the amalgamation of exercise therapy with low-frequency pulse electrical stimulation can significantly improve clinical efficacy, promote nerve function, and muscle strength recovery, and features a high safety profile. Relevance to clinical practice The combination of exercise therapy and low-frequency pulsed electrical stimulation can notably improve the promotion of neurologic function and muscle strength recovery in patients with humerus shaft fractures and radial nerve injuries with a high degree of safety. Clinical trial registration:https://www.researchregistry.com, identifier researchregistry9461.